2016
DOI: 10.2196/ijmr.4295
|View full text |Cite
|
Sign up to set email alerts
|

YouTube Videos to Create a “Virtual Hospital Experience” for Hip and Knee Replacement Patients to Decrease Preoperative Anxiety: A Randomized Trial

Abstract: BackgroundWith declining reimbursement to health care systems, face-to-face time between patients and providers to optimize preoperative education and counseling may be challenging.ObjectiveBecause high patient anxiety prior to surgery has been linked to more severe and persistent pain after joint replacement surgery, the Orthopedic Surgery Department at Mayo Clinic in Florida created a playlist of 16 YouTube videos aimed at creating a virtual hospital experience for primary total hip and knee joint replacemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 27 publications
0
40
0
1
Order By: Relevance
“…A group at the Mayo Clinic created a set of videos for patients with the goal of counselling and optimizing preoperative education prior to hip and knee replacement surgery. Their randomized controlled trial revealed that patients' anxiety levels were less if the videos had been viewed [50]. This study demonstrates the impressive seemingly endless power and reach of social media [50].…”
Section: Youtube and Vimeo: Social Media Portals For Video Sharingmentioning
confidence: 75%
See 1 more Smart Citation
“…A group at the Mayo Clinic created a set of videos for patients with the goal of counselling and optimizing preoperative education prior to hip and knee replacement surgery. Their randomized controlled trial revealed that patients' anxiety levels were less if the videos had been viewed [50]. This study demonstrates the impressive seemingly endless power and reach of social media [50].…”
Section: Youtube and Vimeo: Social Media Portals For Video Sharingmentioning
confidence: 75%
“…Their randomized controlled trial revealed that patients' anxiety levels were less if the videos had been viewed [50]. This study demonstrates the impressive seemingly endless power and reach of social media [50]. For someone new to social media, it can be quite overwhelming such that searching for 'ASCRS surgery' in the toolbar results in over 26 000 results including various society videos, podium presentation from past meetings or any media tagged with the ASCRS name, making this a valuable encyclopaedia of videos.…”
Section: Youtube and Vimeo: Social Media Portals For Video Sharingmentioning
confidence: 99%
“…We selected 34 trials with 3742 participants, of which 29 were randomised, controlled , 4 were quasi‐randomised and 1 was cluster‐randomised (Figs. and ; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with an inadequate understanding of the language used to transmit information were not studied in these trials. The effects of different information formats were tested by 30 trials and different timings by 5 trials .…”
Section: Resultsmentioning
confidence: 99%
“…Healthcare professionals have begun to use YouTube as a tool for patient education in certain areas,2 but the volume of professionally created content is far outweighed by content that is created by YouTube users who are not healthcare professionals. As videos are often not peer reviewed, there is a wide variation in the quality and reliability of videos available.…”
Section: Introductionmentioning
confidence: 99%